Case Study on the Impact of Workload, Motivation, and Discipline on Employee Performance at PT. Caturkarda Depo Bangunan, Tbk - Bancin, Modesta; Susilo, Sophia Reni; Anatasia, Velly (Journal of Business & Applied Management, 2025)
This study investigates the impact of workload, work motivation, and work discipline on employee performance within the receiving division of PT. Caturkarda Depo Bangunan Tbk, a building materials retailer in Indonesia.  A significant decline in this division's performance, from "Excellent" to "Fair" between January and June 2024, prompted this research.  The study's novelty lies in examining the interplay of these three factors within this specific organizational context, addressing inconsistencies in prior research regarding their impacts on performance.  Employing a quantitative approach, primary data were collected through questionnaires (n=85) and interviews with the division manager.  Path analysis using SmartPLS 4 was utilized to analyze the data.  The findings reveal a significant positive relationship between workload and employee performance (p=0.008), supporting Hypothesis 1.  However, contrary to expectations, work motivation did not significantly influence performance (p=0.532), rejecting Hypothesis 2.  Hypothesis 3 was supported, demonstrating a significant positive relationship between work discipline and employee performance (p=0.000).  The R-squared value of 0.770 indicates that 77% of employee performance variance is explained by the three examined variables.  The study concludes that while workload and work discipline significantly affect employee performance in this context, work motivation requires further investigation and potential intervention strategies to enhance its impact.  The results provide valuable insights for PT. Caturkarda Depo Bangunan Tbk to improve its employee performance by focusing on workload management and reinforcing work discipline.